2003
DOI: 10.1590/s1413-86702003000200003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ticarcillin/clavulanic acid versus ceftriaxone plus amikacin for fever and neutropenia in pediatric patients with leukemia and lymphoma

Abstract: Background. The empirical use of antibiotic treatments is widely accepted as a means to treat cancer patients in chemotherapy who have fever and neutropenia. Intravenous monotherapy, with broad spectrum antibiotics, of patients with a high risk of complications is a possible alternative. Methods. We conducted a prospective open-label, randomized study of patients with lymphoma or leukemia who had fever and neutropenia during chemotherapy. Patients received either monotherapy with ticarcillin/clavulanic acid (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…6 Body temperature is most usually evaluated by axillary measurement in Brazil, and oral or anal measurements are only rarely made. 6 Body temperature is most usually evaluated by axillary measurement in Brazil, and oral or anal measurements are only rarely made.…”
Section: Definitionsmentioning
confidence: 99%
“…6 Body temperature is most usually evaluated by axillary measurement in Brazil, and oral or anal measurements are only rarely made. 6 Body temperature is most usually evaluated by axillary measurement in Brazil, and oral or anal measurements are only rarely made.…”
Section: Definitionsmentioning
confidence: 99%
“…Broad-spectrum antipseudomonal cephalosporins (such as ceftazidime [7] and cefepime [8][9][10][11][12][13][14]), carbapenems (such as imipenem-cilastatin [15,16] and meropenem [17][18][19][20][21][22][23][24][25][26][27][28][29]), and b-lactam-b-lactamase inhibitor combinations (such as ticarcillin clavulanate [13,30,31] and piperacillintazobactam [10,17,[32][33][34][35][36][37]) have been evaluated as monotherapy in this setting. The Spanish and German guidelines support choices from each antibiotic class, whereas the American guidelines have not recommended b-lactam-b-lactamase inhibitor agents, such as piperacillin-tazobactam, as monotherapy, citing limited experience with these agents when the guidelines were published in 2002 [2].…”
mentioning
confidence: 99%
“…The Spanish and German guidelines support choices from each antibiotic class, whereas the American guidelines have not recommended b-lactam-b-lactamase inhibitor agents, such as piperacillin-tazobactam, as monotherapy, citing limited experience with these agents when the guidelines were published in 2002 [2]. Since then, further studies have been published that show that these agents have an important role in treatment [10,13,17,[30][31][32][33][34][35][36][37]. Here, we report the results of a large, multicenter, multinational, open-label, randomized-controlled clinical trial that examines the safety and efficacy of piperacillin-tazobactam monotherapy, compared with cefepime, for the empirical treatment of fever in neutropenic patients with cancer.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] Furthermore, exceedingly small numbers of patients in these studies had culture-proven Gram-negative bacteremia, making comparisons between the 2 empirical treatment strategies difficult. If there is a benefit of empirical combination therapy, it is unknown whether it extends to all children or whether this approach should be reserved for particular subgroups such as severely ill patients, profoundly neutropenic patients, or patients with risk factors for multidrug-resistant organisms.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] Kumar and colleagues conducted a retrospective, propensity-matched multicenter cohort study in the adult ICU population and found that empirical combination therapy was associated with decreased 28-day mortality. This benefit was most pronounced for early generation cephalosporins but did not persist when b-lactams with broader spectrums of activity were prescribed.…”
Section: Discussionmentioning
confidence: 99%